Care for evacuated children - Саипова, K (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
In this article, the author closes the concern for evacuated children from frontline territories that were evacuated to the territory ofUzbekistan during the Second World War. The republic rendered great assistance in accepting and accommodating evacuated children, providing them with first aid, and opening orphanages. In August 1941, trains with an evacuated population began to arrive in Uzbekistan, the Council of People's Commissars of the Republic adopted a resolution on the organization of a commission for their reception and arrangement. Residents of the republic showed great care for them, helped with housing, food, clothing. Particularattention was paid to evacuated children who lost their parents. The republic accepted in the autumn of 1941 one and a half million evacuated. Among them, 200 thousand children, half of whom were orphans